2022
DOI: 10.1177/10497315221118109
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative System Dynamics Modeling to Support Community Planning in Opioid Overdose Prevention

Abstract: Purpose: We aimed to help community stakeholders develop a shared understanding of the opioid crisis through qualitative system dynamics (SD) modeling to inform local strategies for prevention and treatment. Methods: As part of the HEALing Communities Study-New York State, we used secondary qualitative data from community stakeholder interviews and coalition meeting notes to develop qualitative SD models that elucidate the interdependencies and feedback structures underlying the opioid epidemic in each communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Group model building (GMB) is a participatory approach to SD modeling, which has been used to study a variety of complex social issues, including health disparities, structural racism, stigma, and opioid use [ 27 30 ]. Typical GMB programs bring together community members, experts, and other stakeholders to work together with modeling facilitators to build a shared understanding of the forces and feedback processes that explain a complex, dynamic problem [ 25 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Group model building (GMB) is a participatory approach to SD modeling, which has been used to study a variety of complex social issues, including health disparities, structural racism, stigma, and opioid use [ 27 30 ]. Typical GMB programs bring together community members, experts, and other stakeholders to work together with modeling facilitators to build a shared understanding of the forces and feedback processes that explain a complex, dynamic problem [ 25 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The goals of participatory systems science approaches are to build a common vocabulary and agenda to describe a complex problem and its drivers, design potential solutions, and garner buy-in to implement the solutions that rise to the top after a range of options have been assessed with quantitative modeling approaches ( 40 ). For example, participatory systems science approaches have been applied to help community stakeholders in the HEALing Communities Study-New York State (HCS-NY) develop a shared understanding of the opioid crisis in order to inform local strategies for prevention and treatment ( 41 ). Community stakeholders who participated in the New York effort reported that the causal mapping approach helped them see the interconnectivity of complex factors, actors, and sectors and appreciate the need for multiple, mutually reinforcing strategies to avert opioid overdose and fatality.…”
Section: Addressing Complexity With Systems Sciencementioning
confidence: 99%
“…The goals of participatory systems science approaches are to build a common vocabulary and agenda to describe a complex problem and its drivers, design potential solutions, and garner buy-in to implement the solutions that rise to the top after a range of options have been assessed with quantitative modeling approaches (40). For example, participatory systems science approaches have been applied to help community stakeholders in the HEALing Communities Study-New York State (HCS-NY) develop a shared understanding of the opioid crisis in order to inform local strategies for prevention and treatment (41).…”
Section: Addressing Complexity With Systems Sciencementioning
confidence: 99%